A Systematic Literature Review: Muslim Friendly Tourism Based on Hepta Helix - Soehardi, Dwi Vita Lestari; Soemitra, Andri; Abd Majid, M Shabri (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
Muslim-friendly tourism has emerged as a rapidly growing segment in the global tourism industry, driven by the increasing number of Muslim travelers seeking services that align with Islamic values. However, the development of this sector still faces fragmented coordination among stakeholders and the lack of a comprehensive collaborative framework. This study aims to review and map the scientific literature on the development of Muslim-friendly tourism using a Systematic Literature Review (SLR) approach and to analyze the integration of the Hepta Helix model in its management practices. The Hepta Helix model involves seven key stakeholders—government, academia, business actors, community, media, non-governmental organizations (NGOs), and technology—as strategic elements in shaping an inclusive and sustainable halal tourism ecosystem. This study examines articles published between 2021 and 2024, sourced from databases such as Scopus, Google Scholar, and ERIC, using keywords including “Muslim-friendly tourism,” “halal tourism,” and “Hepta Helix.” The findings indicate that most studies remain focused on conceptual aspects and basic halal tourism services, while collaborative integration among actors within the Hepta Helix framework is still rarely discussed explicitly. These results highlight an urgent need for strengthened cross-sector coordination, supportive regulation, and the utilization of digital technology to enhance the competitiveness of halal tourism at both local and global levels. This study is expected to contribute to the development of more integrative policy and research directions in the field of Islamic value-based tourism studies.